Strategies used in comprehending English idioms by EFL students from China / Wu Mei Na - Wu, Mei Na (2016)
Idioms are essential parts of languages and for the English as Foreign Language (EFL) learners in The People's Republic of China (PRC), learning and comprehending English idioms are the bigger challenges. The study is to ascertain strategies employed by participants in comprehending English idioms, as well as to ascertain whether an individual’s English vocabulary knowledge level would help him/her to comprehend the English idioms. Thus participants’ Vocabulary Level Test (VLT) results were used to categorize participants into two groups by following Liu’s (2010) method. In addition, three participants from each of the two groups were asked to do the Think-Aloud protocol (TAP) while they were doing the Idiom Recognition Test (IRT). The data for the first research question were analysed based on Lakoff’s (1987) theory and Copper’s (1999) and Liu’s (2010) researches to investigate the types of strategies used by PRC EFL learners when they try to comprehend unfamiliar English idioms. The findings show that there are eleven (11) types of strategies used by PRC EFL learners. For the second research question, the data from the two groups were used to determine if an individual’s English vocabulary knowledge level would help participant to comprehend the English idioms. The findings show that when participants had a higher level of English vocabulary knowledge, there was a corresponding high level of comprehension of idioms as well.